TRADISI DAN NILAI BUDAYA PEMBACAAN KITAB ALBARZANJI - Furoidatul Husniah (FKIP Universitas Islam Jember, 2015)
In indonesia Berzanji or dibaan is an activity that has uniqueness in terms of reading and also has high values in each rhyme or nadhom. Cultural values includes the religious values of Iman, social values that built to strengthen the t6ies of Islamic brotherhood when read the book albarzanji or diba’, personality values that can be revealed from the understanding of the content of it that describes the prophet Muhammad as the exemplary figure that can be the role model of all his behavior, and the educational values for young generation they have to preserve from the culture of reading barzanji or dibaan. Those values are in accordance with national character of Indonesia, togetherness, having good moral and good personality and always preserve in keeping this great tradition from time to time.Keywords: albarzanji , reading , cultural values